Grain yield assessment of 55 triticale lines in the Mexicali Valley - Velasco-López, Velasco-López; Ruiz-Torres, Norma Angélica; Sosa-Flores, Mayra Alejandra; Aíl-Catzim, Carlos Enrique; Sánchez-Ramírez, Francisco Javier (Revista Mexicana de Ciencias Agrícolas, 2025)
Triticale in the arid and semiarid regions of Mexico is postulated as an alternative crop to corn and wheat because it produces forage and grain of ideal quality for livestock feed, and the new varieties show grain yield potential similar to wheat. Therefore, this study aimed to evaluate the grain yield and its components in 55 advanced triticale lines in the Mexicali Valley during the autumn-winter 2015-2016 cycle under a randomized complete block design. The results showed 11 triticale lines with yields between 6.5 and 8.3 t ha-1, which were higher than the control, which obtained 3.8 t ha-1. Under the agroecological conditions of this study, it was determined that of the 55 triticale lines evaluated, 11 of them are considered to have grain yield potential since they outperformed the control.